Estimates of the Number of Workers Exposed to Diesel Engine Exhaust in South Korea from 1993 to 2013 - Choi, Sangjun (Saf Health Work, 2016)
BACKGROUND: The aim of this study was to estimate the number of workers exposed to diesel engine exhaust (DEE) by industry and year in the Republic of Korea. METHOD: The estimates of workers potentially exposed to DEE in the Republic of Korea were calculated by industry on the basis of the carcinogen exposure (CAREX) surveillance system. The data on the labor force employed in DEE exposure industries were obtained from the Census on Establishments conducted by the Korea National Statistical Office from 1993 to 2013. The mean values of prevalence rates adopted by EU15 countries were used as the primary exposure prevalence rates. We also investigated the exposure prevalence rates and exposure characteristics of DEE in 359 workplaces representing 11 industries. RESULTS: The total number of workers exposed to DEE were estimated as 270,014 in 1993 and 417,034 in 2013 (2.2% of the total labor force). As of 2013, the industry categorized as “Land transport” showed the highest number of workers exposed to DEE with 174,359, followed by “Personal and household services” with 70,298, “Construction” with 45,555, “Wholesale and retail trade and restaurants and hotels” with 44,005, and “Sanitation and similar services” with 12,584. These five industries, with more than 10,000 workers exposed to DEE, accounted for 83% of the total DEE-exposed workers. Comparing primary prevalence rates used for preliminary estimation among 49 industries, “Metal ore mining” had the highest rate at 52.6%, followed by “Other mining” with 50.0%, and “Land transport” with 23.6%. CONCLUSION: The DEE prevalence rates we surveyed (1.3–19.8%) were higher than the primary prevalence rates. The most common emission sources of DEE were diesel engine vehicles such as forklifts, trucks, and vans. Our estimated numbers of workers exposed to DEE can be used to identify industries with workers requiring protection from potential exposure to DEE in the Republic of Korea.